Size Effects on Pumping Rates in High Microbial versus Low Microbial Abundance Marine Sponges - Michael P. Lesser (Oceans, 2023)
Sponges are increasingly recognized as ecologically important on coral reefs as scleractinian corals decline. Most sponge species can be divided into two symbiotic phenotypes which are characterized as high microbial abundance (HMA) or low microbial abundance (LMA) sponges. Sponge species of HMA or LMA symbiotic phenotypes differ not just in their microbiomes, but in other characteristics, including that LMA sponges actively pump at higher rates than HMA sponges based on a standard normalization to size. This dichotomy has recently been questioned because the size range of LMA sponges used to quantify pumping rates during studies on their trophic ecology were exceedingly small, often less than an order of magnitude. Here, both HMA and LMA sponges, across two to three orders of magnitude in sponge volume (mL) or mass (g) were assessed for allometric relationships between sponge size and pumping rates (Q = mL s−1). The scaling analysis of all data sets combined reveals that HMA sponges scale their pumping rates isometrically with size, while LMA sponges scale their pumping rate allometrically. When HMA species are examined separately, however, tropical HMA sponges scaled isometrically, while temperate HMA sponges scaled allometrically. From an ecological perspective, to quantify differences between HMA and LMA sponges for rate functions of interest (e.g., feeding) it is important to remove the effects of size as a covariate, and adjust the Q values of sponges to a standard volume or mass. For multiple species and geographic locations, this analysis shows that LMA sponges always maintain higher Q values. On tropical coral reefs, the differences between HMA and LMA sponges are intrinsic and constrained by strong evolutionary selection resulting in fixed differences in Q, regardless of sponge size.

Quantifying sponge communities from shallow to mesophotic depths using orthorectified imagery - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Marine Biology, 2023)

Production of phytodetritus by a coral reef sponge increases from shallow to mesophotic depths - Michael P. Lesser; Keir J. Macartney; Marc Slattery (Limnology and Oceanography, 2023)
On Caribbean coral reefs, sponges are important members of the benthic community and have an important role in consuming particulate organic matter (POM) and dissolved organic matter (DOM), with the subsequent production of detritus that is then shunted into a process now referred to as the “sponge‐loop.” An emergent species of sponge commonly found on Caribbean coral reefs, Agelas tubulata , increases in size and growth rate from shallow ( A . tubulata depends largely on heterotrophy across shallow to mesophotic depths and has been shown to utilize detritus on shallow reefs. However, detritus production by A . tubulata on shallow and mesophotic coral reefs has not been previously reported. Here we show, using flow cytometry, that sponge detritus includes a previously unquantified component, phytodetritus. Sponge phytodetritus production was shown experimentally to be greater in sponges from mesophotic depths compared to sponges from shallow coral reefs. Additionally, the size range of this phytodetritus corresponds to the size range of autotrophic picoplankton, primarily prochlorophytes, known to be an important food source for filter‐feeding sponges. Given the known lability of phytodetritus, compared to other more recalcitrant components of the detrital pool, its role in the food web of mesophotic communities combined with the increased availability of live POM, may be an underappreciated component of mesophotic community carbon and nitrogen flow.